Effect of Vitamin B12 Deficiency on Thyroid Function Tests Among Adults Visiting Tertiary Health Care Centre in Eastern Nepal - Ghimire, Nisha; Mukhopadhyay, Soumitra; Limbu, Rekha; Chaudhary , Prabesh Kumar; Shah, Surendra Prasad; Das, Pawan Kumar Lal (Medical Journal of Eastern Nepal, 2024)
Background Vitamin B12 deficiency is commonly observed in hypothyroidism and autoimmune thyroiditis. Low vitamin B12 can disrupt thyroid function. Though the prevalence of this deficiency has been documented in various regions of Nepal, studies in Eastern Nepal are limited. The objective of this study was to assess the percentage distribution of vitamin B12 deficiency among adults visiting the tertiary health care centre in Eastern Nepal and to find out the effect of vitamin B12 deficiency on thyroid function test. Methods This study, conducted at Nobel Medical College from January 2022 to December 2023, was cross-sectional in design and included 379 patients. Subjects underwent general health check-ups, including Vitamin B12 and thyroid function tests. Descriptive analysis was performed, and Pearson’s correlation assessed the relationship between vitamin B12 levels and thyroid hormones. Independent t-tests compared hormone levels between groups. P value < 0.05 was considered as statistically significant. Results The vitamin B12 status distribution was as follows: 62.5% normal (>300pg/ml), 18.2% borderline deficient (200-300pg/ml), and 19.3% deficient (<200pg/ml). Prevalence was higher among females. Group II subjects (vitamin B12 <300pg/dl) had significantly lower mean free triiodothyronine (FT3) levels (2.82±0.742 vs. 3.14±0.49 pg/mL, p=0.003) and higher mean thyroid stimulating hormone (TSH) levels (4.69±3.56 vs. 2.55±1.47 mIU/L, p<0.001) compared to group I (B12 >300pg/ml). Vitamin B12 showed a negative correlation with TSH (p=0.013). Conclusion The study indicates a decrease in FT3 levels and an increase in TSH levels among those with vitamin B12 deficiency or borderline cases